RELAÇÕES ENTRE FATORES DETERMINANTES DA QUALIDADE INDUSTRIAL DO TRIGO - Sartori, Cesar O.; Silva, Jose A. G. d.; Kruger, Cleusa A. M. B.; Carbonera, Roberto; Garcia, Dagmar C. (Salão do Conhecimento, 2013)
Resumo